The development chinese Reading skills using Task based Learning For vocational certificate third years Roi Et technical College - Chinda , Watsana; Saeng-ngam, Kanyawadee (Journal for Developing the Social and Community, 2022)
This study aims to 1) Comparison of Chinese reading aloud using task based learning for students at the vocational certificate third years according to the criteria 75. 2) Comparison of Chinese language learning achievement before and after by using task based learning for students at the vocational certificate third years. The sample groups used in this study were: students at the vocational certificate 3rd years in semester 2, academic year 2020, at department of business computer, consisting 25 people of Roi-Et technical college. The research instruments are: task based based lesson plans, Chinese reading aloud test, achievement test, The statistics used in the data analysis are: percentage, average, standard deviation, static t-test (One sample t-test) and t-test (Dependent sample t-test) The results of the research found that: 1) Chinese reading aloud scores of 25 students in the third year in vocational certificate that has been learned in task based. Students had scores higher than the 75 threshold with statistically significanat .05 level. 2) Before learning with task based. The students had higher academic achievement than before. the statistically significant at the .05 level.